KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD (BSC): STUDI KASUS - Nabella, Nabella; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
Regional General Hospitals as hospitals owned by local governments must provide the best service for the community, one way to assess the performance of the services provided is to use the Balanced Scorecard (BSC) method where this assessment does not only look at the financial perspective. but other aspects in the provision of health services to patients in hospitals. This study aims to see the results of the application of the use of the Balanced Scorecard (BSC) in the performance analysis of hospitals in Indonesia. This study uses a literature review method. Based on a study conducted by looking at the 3 journals seen, it was found that several targets had not been achieved in the assessment of several existing perspectives. The results obtained that the lack of budget efficiency in existing hospitals, not realizing the planned budget, customer acquisitions that do not increase causing new customers to not increase significantly, not achieving several hospital indicators and lack of productivity of hospital employees. The application of the BSC is very important for health services to assess and see which aspects need to be improved by the RSUD as a provider of health services to patients who receive services, the BSC does not only look at the profitability of the hospital but also customer satisfaction in existing health care facilities.